First Harrison Gray Otis house at 141 Cambridge Street, ca. 1961 - Woodman, W.C. (Tufts Archival Research Center, 2005)
Street-level view of the first Harrison Gray Otis house, located at 141 Cambridge Street at the northwest corner of Cambridge and Lynde Streets. The facade of the house faces south towards Cambridge Street. A wrought-iron fence and gate surrounds the front of the property. Both a street sign as well as a sign for the Society for the Preservation of New England Antiquities (SPNEA) hangs from the iron fence in front of the house. A bus stop sign stands on the side walk to the south of the Otis house. Designed by Charles Bulfinch, 1795-96 4 5/8 x 4 13/16, 5 x 5 1/8 overall Photographs